2021
DOI: 10.1093/jimb/kuab059
|View full text |Cite
|
Sign up to set email alerts
|

Basic and applied research on multiple aminoglycoside antibiotic resistance of actinomycetes: an old-timer's recollection

Abstract: A list of our research achievements on multiple aminoglycoside antibiotic (AG) resistance in AG-producing actinomycetes is outlined. In 1979, the author discovered a novel AG (istamycin)-producing Streptomyces tenjimariensis SS-939 by screening actinomycetes with kanamycin (KM)-resistance and plasmid profiles. This discovery directed our biochemical and genetic approaches to multiple AG resistance (AGR) of AG producers. In this article, the following discoveries will be outlined: 1. AGR profiles correlating wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Actinomycetes are a diverse group of microorganisms that are rich in valuable chemical compounds. For example, the antibiotics they produce are critical for the protection of plants, animals, and humans from harmful microorganisms [41][42][43][44]. Streptomyces species are the main microbes used for the biocontrol of plant diseases because of their wide host range.…”
Section: Discussionmentioning
confidence: 99%
“…Actinomycetes are a diverse group of microorganisms that are rich in valuable chemical compounds. For example, the antibiotics they produce are critical for the protection of plants, animals, and humans from harmful microorganisms [41][42][43][44]. Streptomyces species are the main microbes used for the biocontrol of plant diseases because of their wide host range.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Streptomyces sp. PBR36 contains smBGCs that encode for ulleungmycin [ 99 ], griseoviridin [ 100 ], tylactone [ 101 ], and istamycin [ 102 ], all of which have antimicrobial activity against MDR bacterial pathogens. PBR36 also encodes the biosynthesis of abyssomicin C and actinomycin D gene clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The strains of Streptomyces genus employ their secondary metabolites as weapons to inhibit phytopathogenic fungi ( Amin et al, 2021 ; Hotta, 2021 ; Mahasneh et al, 2021 ; Terra et al, 2021 ). In this study, genome sequencing revealed that the chromosome of the St. albidoflavus St-220 contained 21 conserved biosynthesis gene clusters (BGCs), of which 10 showed high similarities in structure with known BGCs encoding terpenes, non-ribosomal peptides, polyketides, siderophores, and ectoines, which had been proven to participate in the regulation of antimicrobial activities of Streptomyces strains ( van Bergeijk et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%